Air velocity influences heat storage and core temperature independently of fluid ingestion in humans cycling in hot, humid conditions - Saunders, A. G.; Dugas, J. P.; Tucker, R.; Lambert, M. I.; Naokes, T. D. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Laboratory studies have established that increasing levels of dehydration lead to a proportional increase in body temperature during exercise (Montain and Coyle, 1992). Accordingly it has been concluded that dehydration is one of the most important factors influencing heat regulation during exercise. Field studies of athletes involved in competitive marathon, ultramarathon and ultratriathlon events have however found no such relationship (Sharwood et al., 2002). An important difference is that in out of doors competition, the presence of an adequate windspeed will influence heat loss by convection and evaporation. The aim of our study was to determine (i) the effects of different facing air velocities on body temperature and heat storage during exercise in hot environmental conditions and (ii) the effects of ingesting fluids at different rates on body temperature and heat storage during exercise in hot conditions with higher facing air velocities. Methods We submitted a group of male cyclists (n =9) to four cycle trials in hot conditions (33.0 ± 0.4 oC; 59 ± 3 % RH) while the windspeed varied from 0 to 150% of the cyclist`s calculated roadspeed, and 60% of the estimated fluid losses were replaced. In a fifth condition, subject`s replaced 80% of their sweat losses while windspeed was maintained at 100% of the calculated roadspeed. During each trial, heat storage was calculated, and rectal and skin temperatures, heart rate, sweat rates and ratings of perceived exertion (RPE) were measured. Results Heat storage (Fig 1), calculated core temperature, rectal and skin temperatures, heart rate and RPE were significantly increased in the 0 km h-1 condition compared to all other conditions. There were no differences in body temperature or any other measured variable between the 100% windspeed and 150% windspeed condition, or between the 60% and 80% fluid replacement trials (Fig 2). In hot conditions with low air velocity, the ability of the body to lose heat is limited by the evaporative capacity of the environment. At higher air velocities, evaporative capacity of the environment, and therefore heat dissipation, is increased and heat storage and core body temperature are reduced. A higher rate of fluid ingestion did not influence heat storage, core temperature, sweat rate or heart rate in hot conditions when air velocity was equal to the alculated road speed.